THE ROLE OF THE SERVICE SECTOR IN POVERTY REDUCTION AND EMPLOYMENT GROWTH - Fozilov Vahobjon Akrom o’g’li, (TADQIQOTLAR, 2026)
Annotation.  This  article  examines  the  role  of  the  service  sector  in  poverty reduction and employment growth within the modern economy. The study analyzes the contribution of service industries to economic development, income generation, labor market expansion, and improvement of living standards. Particular attention is given to the importance of tourism, finance, trade, education, healthcare, and digital services in  creating  new  jobs  and  increasing  household  incomes.  The  article  also  explores government  policies  and  institutional  mechanisms  aimed  at  supporting  the  service sector as an important tool for sustainable economic growth and poverty alleviation.